Cross-sectional multimedia audit reveals a multinational commercial milk formula industry circumventing the Philippine Milk Code with misinformation, manipulation, and cross-promotion campaigns - Capili, Donna Isabel S.; Datu-Sanguyo, Janice; Mogol-Sales, Claire S.; Zambrano, Paul; Nguyen, Tuan T.; Cashin, Jennifer; Mathisen, Roger (Frontiers in Nutrition, 2023)
The Philippine Milk Code was enacted in 1986 to protect breastfeeding and reduce inappropriate marketing of breastmilk substitutes. The Philippine Milk Code is categorized as “substantially aligned” with the International Code of Marketing of Breast-milk Substitutes (“the Code”), but its provisions are assessed as relatively weak in prohibiting promotion to the general public. The extent to which violations of the Philippine Milk Code persist in traditional media platforms and in the digital space has not been systematically explored. This study was conducted to examine the marketing and promotion of products under the scope of the Code, as well as those regulated by the Philippine Milk Code. Through a media monitoring conducted from March–September 2018, a total of 430 unique TV (n=32), printed (n=87) and online (n=311) promotional materials were identified. A coding tool was used to analyze the content, including the marketing elements used in the materials. Our findings show that commercial milk formula (CMF) for children ≥36 months old was the most promoted type of product (n=251); and staging of events (n=211), provision of special discounts or financial inducements (n=115) and the use of taglines were the most used marketing elements. Promotion of CMF for children <36 months old was uncommon, which supports the conclusion that there is broad compliance with the Philippine Milk Code in terms of the types of products promoted. However, analysis of marketing elements reveals that the commercial milk formula industry circumvents the Philippine Milk Code through the use of false and misleading health and nutrition claims, emotionally manipulative language in promotional materials, and cross-promotion. The findings indicate gaps in enforcement and regulatory measures that require urgent attention.